Efektifitas Pemberian Pre-Emtif Paracetamol Intravena 1000mg Terhadap Nyeri Pasca Operasi Sectio Caesarea Dengan Anestesi Spinal - Galih Pambayun; Naufal Anasyi; Ayu Rahmawati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background: Pain after cesarean section surgery often results in moderate and severe pain for up to 48 hours. To overcome this pain, pain management is very necessary, namely by providing pre-emptive analgesics, one of the postoperative pain management which refers to drug administration before the pain occurs, in connection with the prevention of sensitization of the central and peripheral nervous system. The use of paracetamol as part of a multimodal technique in postoperative patients can increase the analgesic potency.Methods: This type of experimental research has been carried out on 16 patients who will undergo sectio caesarea surgery. Pre-emptive administration of paracetamol 1000 mg intravenously was given 30 minutes before surgery or pre-incision, after which the pain level was measured using a Numerical rating scale (NRS) by means of observation and interviews 8 hours after surgery, 16 hours and 24 hours. In this study, the data were processed using the Shapiro-Wilk normality test and the Wilcoxon test. Results: The results showed that the majority of respondents experienced moderate pain. This is proven by the majority of 8 hours postoperatively, 13 respondents (81.3%) experienced moderate pain and 11 respondents (68.8%) experienced moderate pain, while at 24 hours the majority had mild pain with 13 respondents (81.3 %). Conclusion: Based on the results of this study, giving 1000 mg intravenous pre-emptive for postoperative cesarean section pain with spinal anesthesia was effective in reducing postoperative cesarean section pain